Water diversion induced changes in aquatic biodiversity in monsoon-dominated rivers of western Himalayas in Nepal: implications for environmental flows - Shah, R.D.T.; Sharma, S.; Bharati, Luna (Elsevier, 2020)
Water diversion projects across the world, for drinking water, energy production and irrigation, have threatened riverine ecosystems and organisms inhabiting those systems. However, the impacts of such projects on aquatic biodiversity in monsoon-dominated river ecosystems are little known, particularly in Nepal. This study examines the effects of flow reduction due to water diversion projects on the macroinvertebrate communities in the rivers of the Karnali and Mahakali basins in the Western Himalayas in Nepal. Macroinvertebrates were sampled during post-monsoon (November), baseflow (February) and pre-monsoon (May) seasons during 2016 and 2017. Nonmetric Multidimensional Scaling (NMDS) was performed to visualize clustering of sites according to percentage of water abstractions (extraction of water for various uses) and Redundancy Analysis (RDA) was used to explore environmental variables that explained variation in macroinvertebrate community composition. A significant pattern of macroinvertebrates across the water abstraction categories was only revealed for the baseflow season. NMDS clustered sites into three clumps: “none to slight water abstraction (< 30% – Class 1)”, “moderate water abstraction (> 30% to < 80% – Class 2)” and “heavy water abstraction (> 80% – Class 3)”. The study also showed that water abstraction varied seasonally in the region (Wilk’s Lambda = 0.697, F(2, 28) = 4.215, P = 0.025, n2 = 0.23). The RDA plot indicated that taxa such as Acentrella sp., Paragenetina sp., Hydropsyche sp., Glossosomatinae, Elmidae, Orthocladiinae and Dimesiinae were rheophilic i.e. positively correlated with water velocity. Taxa like Torleya sp., Caenis sp., Cinygmina sp., Choroterpes sp., Limonidae and Ceratopogoniidae were found in sites with high proportion of pool sections and relative high temperature induced by flow reduction among the sites. Indicator taxonomic groups for Class 1, 2 and 3 water abstraction levels, measured through high relative abundance values, were Trichoptera, Coleoptera, Odonata and Lepidoptera, respectively. Macroinvertebrate abundance was found to be the more sensitive metric than taxonomic richness in the abstracted sites. It is important to understand the relationship between flow alterations induced by water abstractions and changes in macroinvertebrates composition in order to determine sustainable and sound management strategies for river ecosystems.